FORMULASI RECHTSVINDING DENGAN PENALARAN ANALOGIS DALAM EPISTEMOLOGI HUKUM ISLAM (Telaah Metodologis Qiyas sebagai Ra’y terhadap Mashâdir al-Ahkâm asy-Syar’iyyah) - Muhammad Syarif Hidayatullah (Institut Agama Islam Negeri Batusangkar, 2020)
The background of this study is rechtvinding (legal discovery efforts) must be carried out to describe contemporary cases and then establish the law so that there is a legal status.. The qiyas method is a rechtvinding tool with analogical reasoning in the study of the epistemology of Islamic law. Qiyas is the use of ra'y against mashâdir al-Ahkâm asy-Syar'iyyah (al-Qur'an and sunnah) and is one of the secondary legal arguments agreed upon by jumhur scholars. This paper aims to study methodologically the flow of thinking and work patterns of rechtvinding through qiyas. Rechtvinding formulation with the qiyas method is carried out by equating the law of something that has no legal provisions with something that already has legal provisions in the text of the al-Qur'an and sunnah because of the equality of 'illat between the two. In the application of qiyas, there are pillars that must exist, namely ashl, far ', hukm al-ashl and' illat, each pillar has conditions that must be met as legality. With the similarity of 'illat, it can be applied qiyas between ashl to far'. 'Illat is divided into' illat manshushah and 'illat mustanbathah and methodologically there is a method of investigation to find out' illat which is called masâlik al-'Illat.